Reviewer Acknowledgement - Martin Kopp (Bern Open Publishing, 2019)
The practice of peer review is to ensure the research published in Current Issues in Sport Science (CISS) is of the highest standard. Peer review lies at the heart of scholarly publishing and is utilized by all reputable journals. Our referees and section editors play a crucial role in developing the reputation of Current Issues in Sport Science (CISS) to a leading forum for original research in the field. Therefore, I would like to formally thank all who have so willingly and voluntarily contributed to the journal in 2018.